Performance of Broiler Chickens fed Graded Levels of Hibiscus sabdariffa Seed Meal as a Source of Methionine - Maggawa, D. D.; Yusuf, H.B.; Yakubu, B. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
One hundred and fifty (150) broilers chicks at 14 days of age were used in a six (6) weeks feeding trial to determine the effect of feeding graded levels of Hibiscus sabdariffa Seed Meal (HSSM) as a natural source of methionine on performance of broiler chickens. Five broiler starter and finisher diets each were formulated. Diet 1 was the control and contained the DL – methionine, while Diet 2, 3, 4 and 5 contained 2.5%, 5.0%, 7.5% and 10.0% Hibiscus sabdariffa Seed Meal (HSSM), respectively. The birds were randomly allocated to the five treatment diets in a completely randomized design (CRD). The results showed that final weight, body weight gain, daily weight gain, total feed intake and feed conversion ratio in the starter phase were significantly (P<0.05) different across the treatment groups. In the finisher phase, only initial weight, total feed intake and daily feed intake were significantly (P<0.05) affected by the treatment, while final body weight, body weight gain, daily body weight gain and feed conversion ratio were not. Cost of feeding/kg and total cost of feed consumed per bird were least in T1 (#131.00) and highest in T5 (#231.00). Feed cost/kg gain was highest in T5 (#700.30) but least in T1 (#330.67), while total weight gain/kg was highest in T1 (1.24kg), followed by T4 (1.08). This study indicated that replacement of DL – methionine with 2.5% HSSM could result in higher profit margin for poultry farmers. It is therefore recommended that Hibiscuss sabdariffa seed meal be used as a natural source of methionine to replace synthetic methionine at 2.5% level in the diet of broiler chickens.